Implementasi, Efektifitas dan Evaluasi Program Training di PT. Mandiri Utama Finance Cabang Serang - Ratnasari, Henny; Nurasniar, Wahyu Apri; Riesata, Yusuf (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2022)
Training as a form of activity carried out to support the Company's operational activities so that it runs well and maximally in accordance with the provisions and targets of the Company. Training must be carried out in the context of mandatory activities as a support for work activities that can also improve employee performance. The training activities are packaged in the Training Program as a reference for the schedule of activities and materials. This study uses qualitative methods with data collection techniques in the form of interviews and observations. The technique of determining the informants in this research is purposive sampling. The informants in this study were the manager and two supervisors at PT. Mandiri Utama Finance Serang Branch. After collecting data, a triangulation technique is used as a way to match the data obtained. The results of this study are that the methods that have been implemented can be used effectively, including the process of training prospective employees using in-class learning methods and on-the-job training. For employee development, the method used by PT. Mandiri Utama Finance Serang Branch, namely the method of job rotation, planning for a replacement, then reusing the training method (training on the job).